Analisis Risiko Kecelakaan Kerja Dengan Menggunakan Metode Hazop Pada Industri Makanan - Fathoni Thohir; Fibi Eko Putra; Tri Ngudi Wiyatno (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The food industry, particularly the bakery sector, has shown significant growth in Indonesia but still faces various occupational health and safety (OHS) risks, especially during the baking process involving high temperatures and heavy equipment. This study aims to analyze work accident risks in the bread baking process using the Hazard and Operability Study (HAZOP) method. HAZOP is applied to identify potential deviations from normal operational conditions that may lead to workplace accidents. Data were collected through direct observation and literature review, then analyzed using a risk matrix based on Likelihood and Severity levels. The results indicate that the highest risk originates from oven temperature deviations, which may cause burns, heat stress, and fire hazards. The risk levels are categorized as